iBarco Carga - transporte de cargas fluviais na era da transformação digital: estudo de caso no mercado da Amazônia. Rios de oportunidades para seu negócio! - Guimarães, Horácio Betcel (2024)
Digital transformation is a phenomenon that positively impacts society by optimizing processes and increasing efficiency across various sectors. In the Amazon region, freight transportation faces significant challenges, such as delays, bureaucracy, and lack of connectivity, hindering local economies and the integration between clients and vessel owners. This study aims to propose an innovative solution based on science, technology, and innovation to modernize river freight transportation in the Amazon. The methodology involved documentary research, assessment of regional demands, and the development of a functional prototype of the iBarco Carga platform, which connects clients and transport providers in a practical and efficient manner. The results aim to facilitate access to logistics services, promote the region's socioeconomic development, and stimulate digital transformation in the sector. Thus, the proposal contributes to integrating the Amazon into the global technological landscape, generating positive impacts on the economy, education, health, and transportation.